Development of Mass Media Text-Based Instructional Materials to Improve Critical Reading Skills of University Students - Sultan, Sultan; Rofiuddin, Ahmad; Nurhadi, Nurhadi; Priyatni, Endah Tri (Pedagogika, 2018)
Critical thinking competency is one of the requirements for university graduates to succeed. Critical reading skills learning can accommodate the development of the critical thinking competency. Therefore, this study was designed to develop instructional materials for the students to learn the skills. The present study was carried out following some steps of research and development study that includes a preliminary study, the development of product prototype, tryout, and the effectiveness test. This study involved 82 pre-service Indonesian teachers studying at Universitas Negeri Makassar, Indonesia. Data was collected through a questionnaire, an experts’ validation sheet, and a test on critical reading skills. The results of the study indicated that instructional materials developed with a complete and integrated structure, involving the activity of conceptualizing, modeling, and practicing are effective in improving students’ critical reading skills. The characteristics of mass media texts are highly appropriate for habituating students to evaluate, respond to, and reflect on information critically. The instructional materials developed in this study can be used by the university students in learning and support the development of students’ 21st-century learning competency.